Republic of Madagascar : Economic Development Document. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Economic Development Document describes the strategy adopted by the government of Madagascar to reverse the trend of modest economic performance, deteriorating social conditions, and persistent poverty observed in recent years. This strategy addresses the underlying causes of poverty. The primary aim of the fiscal policy is to increase revenue and rationalize budget expenditure to provide ample margins to finance priority spending, specifically social and infrastructure spending. The priorities are to expand the tax base and continuing reform of tax and customs administration, and to eliminate the causes of inefficient public expenditure. The monetary policy is given the role of regulating domestic liquidity to normalize trends in economic activities and achieve the inflation targets of less than 10.0 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet